Factors Associated with the Perception of Prehospital Internship Training of Dental and Other Health Sciences Students in the COVID-19 Context - Alvitez, Juan (2024)
During the COVID-19 pandemic, pre-internship training of Health Sciences students took on an essential role. The shift to virtual practices and a project-based learning approach brought challenges, but also opened doors for adaptation and learning in a constantly evolving healthcare landscape. To determine the factors associated with the perception of Peruvian health sciences students during the period of isolation due to the COVID-19 pandemic regarding their training prior to hospital internship. A Cross-sectional analytical study was performed. Students from professional schools of health sciences who entered the hospital internship 2022 and students from the year prior to the internship from a Peruvian public university were evaluated. Data collection was performed with a 49-question questionnaire. Female participants were more prevalent with 384 (70.98%) students while the medical career had the highest participation with 152 respondents (28.1%) followed by the dental career with 134 (24.77%). In the adjusted logistic regression model no influence of associated factors on students' perception of their preparedness for hospital internship in the isolation period due to the COVID-19 pandemic was found. Peruvian Health Sciences students self-perceive themselves prepared for hospital internship in Comprehensive Care, Prevention, Collaboration and Self-Learning, but less so in Practical Skills, Understanding Science, Interpersonal Skills and Confidence.